Wielofunkcyjność zaimków kto i który jako źródło wyrażeń funkcyjnych - Data, Krystyna (Forum Lingwistyczne, 2015)
The multifunctionality of the pronoun as a source of functional expressions The subject matter of the article is a description of one of the sources of functional expressions – the multifunctionality of the pronoun with reference to the nominal pronoun kto and the adjective pronoun który. The pronoun seems to be the most diversified part of speech because it fails to follow a single exemplary criterion in defining its type category. Also, having a complex internal structure its multifunctionality is demonstrated on various text organization levels. The starting point of the description is the analysis of the contrast between interrogative and relative functions of these pronouns. Considering the multiplicity of the text roles both pronouns kto and który are presented as functional homonyms. The various pronoun roles identified on the text organization level validate thestatement that the multifunctionality of the pronoun is a source of functional expressions. Key words: pronoun, function, homonym, functional expression